Aplikasi Fuzzy Logic untuk Pengambilan Keputusan Pembelian Kendaraan Mobil Menggunakan Metode Mamdani - Nina Andriani; Gunawan; Yosua Tumanggor; Firza Eka Febrianto (Universitas Muhammadiyah Surabaya, 2025)
Vehicles have now become an essential basic need for society. Cars are one of the transportation tools that can be chosen for activities because they can accommodate more than one passenger and offer comfort while driving, eliminating concerns about bad weather during outdoor activities. When purchasing a car, consumers are faced with numerous criteria that influence the selection of the car they want, which makes it difficult for consumers to choose the right car. Several car specifications that consumers consider include the car's weight, passenger capacity, engine size, maximum power, and price. This study discusses the process of recommending the most suitable and needed cars for consumers. By using the fuzzy Tahani method, the processed car data will generate outputs in the form of recommended cars for consumers. This research is expected to assist prospective car buyers in determining the car that best matches their chosen criteria.